An Ameliorated Methodology for Ranking the Tuple (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Many users searching databases through the web in various domains like vehicles, real estate, etc. One of the predicament, we observed in this task is ranking the results retrieved from a database for a user query. The contemporary methods are addressing this problem by sorting the database values. A common line in these methods is that ranking is done in a user and query-independent manner i.e. there is no correspondence between different users queries. We proposed a query and user-dependent approach for ranking query results in relational databases, which is articulating the opinion expressed in query by different users. The designed and developed methodology shows that the ranking of the data in database is constituted depending on the various user opinions i.e. access of tuple through users query expression. The design is based on counting the access of database tuple by users query(ies)